An investigation on different factors influencing firm’s value: Evidence from Tehran Stock Exchange - Hassan Ghodrati; Seyed Reza Ghazi Fini (Management Science Letters)
This paper presents an empirical investigation to evaluate the relationship among firms’ performances including cash, management efficiency and profitability. The proposed study considers eight components of current ratio, acid-test ratio, properties turnover, receivables collection period, earnings per shares, assets flow, return on assets and return on equities. The study selects some firms from Tehran Stock Exchange over the period 2007-2011. Using Spearman correlation ratio as well as regression technique, the study has determined that there was a weak and positive correlation between cash conditions and the firms’ value. In addition, there is a reverse relationship between receivables collection period and the firms’ value. The study has also found some weak relationship between firms’ value and other management efficiency components. Finally, the study has detected some weak and direct relationship between the profitability and firms’ value.